LncRNA SLC7A11-AS1 promotes the progression of hepatocellular carcinoma by mediating KLF9 ubiquitination - Zeng, Fan-Lin; Lin, Jie; Xie, Xing; Xie, Yuan-Kang; Zhang, Jian-Hong; Xu, Daofeng; He, Xiao; Liu, Feng En; Xie, Bin-Hui (Neoplasma, 2023)
Hepatocellular carcinoma (HCC) is a malignant tumor, which seriously threatens the life of patients. LncRNA SLC7A11-AS1 was reported to be abnormally expressed in HCC. Here, the functions and relative molecular regulatory mechanism of SLC7A11-AS1 in HCC were investigated. Nude mice and HCC cells were used as the experimental subjects. Knockdown or overexpression of exogenous genes was conducted in HCC cells. RT-qPCR, IHC, and western blot were employed to evaluate the abundance of genes and proteins. The malignant behaviors were evaluated using CCK-8, clone formation, wound-healing, and Transwell. The locations of SLC7A11-AS1 and KLF9 in cells were determined by FISH and IF assays. The total m6A level was evaluated by dot-blot assay. m6A modification of SLC7A11-AS1 was detected using RNA MeRIP. The interactions among molecules were validated by RIP, ChIP, dual luciferase reporter assay, and co-IP. SLC7A11-AS1 was elevated apparently in HCC cells and HCC tissues from mice. SLC7A11-AS1 silencing could suppress HCC progression, which was validated in in vivo and in vitro experiments. Furthermore, METTL3 mediated m6A modification of SLC7A11-AS1 to elevate its expression. In addition, SLC7A11-AS1 downregulated KLF9 expression by affecting STUB1-mediated ubiquitination degradation and KLF9 enhanced PHLPP2 expression to inactivate the AKT pathway. Eventually, rescue experiments revealed that KLF9 knockdown abolished SLC7A11-AS1 silencing-mediated suppression of HCC progression in vivo and in vitro. Our results unveiled that m6A-modified SLC7A11-AS1 promoted HCC progression by regulating the STUB1/KLF9/PHLPP2/AKT axis, indicating that targeting SLC7A11-AS1 might alleviate HCC progression.